2017
DOI: 10.5194/esurf-5-283-2017
|View full text |Cite
|
Sign up to set email alerts
|

Single-block rockfall dynamics inferred from seismic signal analysis

Abstract: Abstract. Seismic monitoring of mass movements can significantly help to mitigate the associated hazards; however, the link between event dynamics and the seismic signals generated is not completely understood. To better understand these relationships, we conducted controlled releases of single blocks within a soft-rock (black marls) gully of the Rioux-Bourdoux torrent (French Alps). A total of 28 blocks, with masses ranging from 76 to 472 kg, were used for the experiment. An instrumentation combining video ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 37 publications
9
65
0
1
Order By: Relevance
“…On the other hand, smaller R S∕P values ranging from 10 −6 to 10 −5 have been found by Levy et al (2015) for granular flows in Montserrat valleys and by Berrocal et al (1978) for a landslide in Peru. Free-fall laboratory experiments of beads and grains have shown that the seismic energy dissipated during an impact depends on the grain size and velocity, on the nature of the receiving plate, and on the slope angle (Farin et al, 2016, as confirmed by field measurements (Hibert, Malet, et al, 2017). Furthermore, Bachelet et al, (2016Bachelet et al, ( , 2018 have shown that the presence of an erodible bed can decrease the seismic energy transmitted to the ground for free-fall grains, in agreement with field observations of rock impact (Farin et al, 2015).…”
Section: Evolution Of the Rf Activity Compared To The Postcollapse Pementioning
confidence: 82%
“…On the other hand, smaller R S∕P values ranging from 10 −6 to 10 −5 have been found by Levy et al (2015) for granular flows in Montserrat valleys and by Berrocal et al (1978) for a landslide in Peru. Free-fall laboratory experiments of beads and grains have shown that the seismic energy dissipated during an impact depends on the grain size and velocity, on the nature of the receiving plate, and on the slope angle (Farin et al, 2016, as confirmed by field measurements (Hibert, Malet, et al, 2017). Furthermore, Bachelet et al, (2016Bachelet et al, ( , 2018 have shown that the presence of an erodible bed can decrease the seismic energy transmitted to the ground for free-fall grains, in agreement with field observations of rock impact (Farin et al, 2015).…”
Section: Evolution Of the Rf Activity Compared To The Postcollapse Pementioning
confidence: 82%
“…These studies allowed relating the most energetic seismic phases to boulder impacts after a free fall and showed that impacts were characterized by waves packets with frequency contents over the range 1-50 Hz. Controlled releases of single blocks in a marl gully (Hibert et al, 2017) or in quarries (Saló et al, 2018) explored seismic amplitude and energy in relation to the kinetics of block impacts. Hibert et al (2017) inferred single block mass and velocity from local seismic records with a fair accuracy (median ratio between calculated and measured velocity of 0.2).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled releases of single blocks in a marl gully (Hibert et al, 2017) or in quarries (Saló et al, 2018) explored seismic amplitude and energy in relation to the kinetics of block impacts. Hibert et al (2017) inferred single block mass and velocity from local seismic records with a fair accuracy (median ratio between calculated and measured velocity of 0.2). In contrast, Saló et al (2018) did not find a correlation between kinetic parameters of the blocks and measured seismic energies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations